Losing Control. Freedom of the Press in Asia - Williams, Louise (ANU Press, 2014)
'A free press is not a luxury. A free press is at the absolute core of equitable development' according to World Bank President James Wolfensohn. A free press is also the key to transparency and good governance and is an indispensable feature of a democracy. So how does Asia rate? In Losing Control, leading journalists analyse the state of play in all the countries of North Asia and Southeast Asia. From the herd journalism of Japan to the Stalinist system of North Korea, Losing Control provides an inside look at journalism and freedom of the press in each country. One conclusion - a combination of new technology and greater democracy is breaking the shackles that once constrained the press in Asia. 'Brings together Asia's best and brightest observers of the press.' Hamish McDonald, Foreign Editor, The Sydney Morning Herald ' A rare insiders' view exposing the real dynamics behind social and political change in Asia.' Evan Williams, Foreign Correspondent, ABC TV 'A timely and necessary contribution to the debate over the quality of freedom in Asia.' Geoffrey Barker, The Australian Financial Review